Modulation of Biomaterial‐Associated Fibrosis by Means of Combined Physicochemical Material Properties - Lisa E. Tromp; Torben A.B. van derBoon; Roderick H.J. deHilster; Ruud Bank; Patrick van Rijn (Advanced Science)
Abstract Biomaterial‐associated fibrosis remains a significant challenge in medical implants. To optimize implant design, understanding the interplay between biomaterials and host cells during the foreign body response (FBR) is crucial. Material properties are known to influence cellular behavior and can be used to manipulate cell responses, but predicting the right combination for the desired outcomes is challenging. This study explores how combined physicochemical material properties impact early myofibroblast differentiation using the Biomaterial Advanced Cell Screening (BiomACS) technology, which assesses hundreds of combinations of surface topography, stiffness, and wettability in a single experiment. Normal human dermal fibroblasts (NHDFs) are screened for cell density, area, and myofibroblast markers α‐smooth muscle actin (α‐SMA) and Collagen type I (COL1) after 24 h and 7 days of culture, with or without transforming growth factor‐beta (TGF‐β). Results demonstrated that material properties influence fibroblast behavior after 7 days with TGF‐β stimulation, with wettability emerging as the predominant factor, followed by stiffness. The study identified regions with increased cell adhesion while minimizing myofibroblast differentiation, offering the potential for implant surface optimization to prevent fibrosis. This research provides a powerful tool for cell‐material studies and represents a critical step toward enhancing implant properties and reducing complications, ultimately improving patient outcomes.